An integrated functional and transcriptomic analysis reveals that repeated exposure to diesel exhaust induces sustained mitochondrial and cardiac dysfunctions. (March 2019) - Karoui, Ahmed; Crochemore, Clément; Mulder, Paul; Preterre, David; Cazier, Fabrice; Dewaele, Dorothée; Corbière, Cécile; Mekki, Malik; Vendeville, Cathy; Richard, Vincent; Vaugeois, Jean-Marie; Fardel, Olivier; et al.
Abstract: Diesel exhaust (DE) contributes to air pollution, an important risk factor for cardiovascular diseases. However, the mechanisms by which DE exposure induces cardiovascular dysfunction remain unknown and there is still debate on the contribution of the primary particulate matter (PM) fraction compared to the gaseous phase. Although the mitochondria play a key role in the events leading to cardiovascular diseases, their role in DE-induced cardiovascular effects has not been investigated. The aim of this study was to highlight cardiac and mitochondrial events that could be disrupted following acute and/or repeated DE exposures and the contribution of gaseous pollutants to these effects. To address this question, Wistar rats were exposed to DE generated under strictly controlled and characterized conditions and extracted upstream or downstream of the diesel particulate filter (DPF). Evaluation of the cardiac function after acute DE exposure showed a disturbance in echocardiographic parameters, which persisted and worsened after repeated exposures. The presence of the DPF did not modify the cardiovascular dysfunction revealing an important implication of the gas phase in this response. Surprisingly, redox parameters were not altered by DE exposures while an alteration in mitochondrial oxidative capacity was observed. Exploration of the mitochondrial function demonstrated a more specific alteration in complex I of the respiratory chain after repeated exposures, which was further confirmed by transcriptional analysis of left ventricular (LV) tissue. In conclusion, this work provides new insights into cardiovascular effects induced by DE, demonstrating a cardiac mitochondrial impairment associated with the gaseous phase. These effects suggest deleterious consequences in terms of cardiac function for vulnerable populations with underlying energy deficit such as patients with heart failure or the elderly. Graphical abstract: Image 1 Highlights: Acute and repeated diesel exhaust (DE) exposures induced a cardiac dysfunction in rats. Repeated DE exposures induced a decrease in OXPHOS capacity. OXPHOS defect is associated with a decrease in complex I activity. Both whole DE and gaseous phase contribute to these cardiac and mitochondrial defects. Parameters related to cardiac oxidative stress are not affected in these conditions. Abstract : Diesel exhaust induces an acute cardiovascular response, which leads to a sustained cardiac mitochondrial defect and cardiac dysfunction after repeated exposures.